Kāmākhyā māhātmyam - Pāṇḍā, Śibakrshṇaśarmmā; Pāṇḍā, Bishṇukāntaśarmmā (Śibakrshṇaśarmmā Pāṇḍā o Bishṇukāntaśarmmā Pāṇḍā, 1922)
Hymns to Kāmākhyā, Hindu goddess of love, (Her chief shrine also called Kāmākhyā, in the vicinity of Gauhati, Assam), culled from various sources, with exposition in Bengali and instructions for worship.